Climate change impact on Indonesian firm value: Exploring the moderating role of accounting conservatism - Sayuti, Alfian; Farizal Mohammed, Nor; Susanti Amirrudin, Mira (Edelweiss Applied Science and Technology, 2024)
Climate change is one of the risks that can occur in countries across the equator, such as Indonesia. Apart from its geographical location, the industrial sector is one of Indonesia’s highest contributors to emissions. This research examines the impact of climate change and greenhouse gas (GHG) emissions on firm value, moderated by accounting conservatism. Firm value is measured by Tobin’s Q and the market-to-book ratio. The sample consists of high-profile manufacturing industries listed on the Indonesia Stock Exchange in 2020-2021, totalling 208 companies. The results show that climate change, GHG emission issues, and accounting conservatism significantly affect firm value, both directly and moderately. Furthermore, firm value measured using the market-to-book ratio is more sensitive than when measured using Tobin’s Q. This study provides a different perspective on sustainability issues and contributes to signalling theory by testing non-financial and financial performance using the same model. To improve sustainability performance, firms and governments should consider the research findings when developing policies and regulations addressing environmental challenges.